Of prelates and princes a study of the economic and social position of the Tudor episcopate - Heal, Felicity 1945- (Cambridge Cambridge University Press, 1980)
The Tudor bishops were men of power and influence within the English realm, both because they possessed spiritual authority and because they exercised lordship over great estates. This book examines their activities as temporal lords: it seeks to discover how wealthy they were and to what uses their revenues were put. Dr Heal draws upon much research undertaken by other scholars in particular dioceses and for particular prelates. The bishops possessed considerable wealth, but they had little security, for the crown effectively controlled their economic destiny, especially after the break with Rome in 1534. No study of the episcopate can therefore ignore the effects of royal policy, and this book combines an investigation into the attitudes and behaviour of the Tudor monarchs with its close examination of the fortunes of the bishops.
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte 1500-1600; Bishops -- England; Bishops -- England; Reformation; Anglikanische Kirche; Kirchliches Amt; Bischof; Bishops ; England; England ; Church history ; 16th century; Great Britain ; History ; Tudors, 1485-1603; England -- Church history, 16th century; Great Britain -- History, Tudors, 1485-1603.; Great Britain -- History -- Tudors, 1485-1603; England -- Church history -- 16th century; England